Nadir creatinine predicts long-term bladder function in boys with posterior urethral valves. Issue 2 (April 2022) - Delefortrie, T.; Ferdynus, C.; Paye-Jaouen, A.; Peycelon, M.; Michel, J.L.; Dobremez, E.; El Ghoneimi, A.; Harper, L.
Summary: Introduction: Posterior urethral valves (PUV) cause lower urinary tract obstruction leading to increased intravesical pressure during fetal urinary tract development. Though the bladder and kidneys are separate organs, with different embryological origins, they are complementary and influence each other both before and after birth. We aimed to assess the relationship between renal and bladder function in boys with PUV and whether early renal markers could predict future bladder function. Patients and methods: We included all boys with prenatally suspected lower urinary tract obstruction, born between 2000 and 2013, in two University Hospitals, with at least 5 years follow-up. We excluded patients who presented a Lower Urinary Tract Obstruction other than PUV, children who presented multiple birth defects and neonatal deaths and those with incomplete long-term renal or bladder function data. We included data on nadir creatinine (NC), long-term renal function and long-term bladder function (defined by Uroflow parameters). Boys with PUV were divided into three severity groups for renal function according to their NC and three severity groups for bladder function as determined by Uroflow. Results: We included 73 boys. Average nadir creatinine was 43.4 ± 26.1 μmol/L. Twenty-nine boys (49.3%) presented a NC < 35 μmol/L, thirty-eight (52.1%) a NC between 35 and 75 μmol/L, and 6 (8.2%) a NC > 75 μmol/L. Thirty-eight (52.1%) presented normal bladder function, 23 (31.5%) presented moderately impaired bladder function and 12 (16.4%) presented severely impaired bladder function. 41.4% of boys with NC < 35 had abnormal bladder function vs 46.2% of those with an NC between 35 and 75 μmol/L and 83.3% of boys with NC > 75 μmol/L. Nadir creatinine both predicted both bladder function and renal status (table 1). Correlation between presence of grade 3–5 CKD and poor uroflow was also significant (p < 0.005). Discussion: Nadir creatinine was significantly correlated to bladder function at 5 years of age. What this study suggests is that as nadir creatinine increases so does the risk of severe bladder dysfunction. Our results, though limited to flowmeter and renal function, could help pediatric urologist tailor bladder function monitoring, and indicate which patients could benefit from more aggressive bladder therapy. Conclusion: Bladder and renal function are linked in boys with posterior urethral valves. Boys with high nadir creatinine could benefit from early bladder function evaluation and management.